Knowledge, practice, subject: psychoanalytic office in Idilio journal - Savio, Karina (2017)
This article studies the psychoanalytic consultancy "El psicoanalisis le ayudara" that is included in the magazine Idilio between 1948 and 1951 with the purpose of analyzing the modalities that this knowledge adopts in the beginning of its installation in the Argentine society. With this aim, taking into account the discourse studies, we consider three aspects: the way in which the epistolary clinical device is constructed, the senses that psychoanalysis acquires as a discursive object and the enunciation subject that is created in these pages. From this analysis, we have been able to determine that in the clinical device configuration the psychoanalysis is presented as a scientific truth, which aims at adaptation and does not question the social order imposed on women. The voice of the subject-psychoanalyst emerges in this framework as a voice of authority, through which a dissymmetric position is generated with the readers.